Uji Aktivitas Protein Larut Air Umbi Porang (Amorphophallus muelleri Blume) terhadap Escherichia coli dan Staphylococcus aureus - Putu Gita Maya Widyaswari Mahayasih; Tri Handoyo; Mochammad Amrun Hidayat (UPT Percetakan dan Penerbitan Universitas Jember, 2014)
The objective of this study was to determine antibacterial activity of water soluble protein of Porang (Amorphalus muelleri Blume) tuber. The water soluble protein extract was tested against both Eschericia coli and Staphylococcus aureus using filter paper disk method. The inhibition zone of bacterial growth was calculated for both of bacterial cultures. It was found that water soluble protein exhibited antibacterial activity at linear range 0.3-1.9 μg and 0.1-1.9 μg for E. coli and S. aureus respectively, sugesting that S. aureuswas more susceptible than E. coli to this protein. From the electrophoretic profile using 12.5% sodium dodecyl sulfate (SDS) and comassie blue staining (CBS), two protein bands were observed with molecular weight 17 and 19 kDa respectively. The water soluble protein were further evaluated using periodic acid staining (PAS). Pink band with molecular weight 250 kDa and > 250 kDa was found in PAS profile, sugesting the availability of carbohydrate molecule in water soluble protein extract of porang tubers.